The magic finger - Dahl, Roald; Du Bois, William Pene, 1916- illus (New York : Harper & Row, 1966)
Angered by a neighboring family's sport hunting, an eight-year-old girl turns her magic finger on them.
3-6
560L
N
3.5
Keywords: Hunting -- Fiction; Magic -- Fiction; Magic -- Juvenile fiction; Hunting -- Juvenile fiction; Fantasy fiction